Aspects of Form and Genre in the Poetry of Edwin Morgan. - Edgecombe, Rodney Stenning (Cambridge Scholars Pub., 2003)
Edwin Morgan was born in 1920 in Glasgow and studied at Glasgow University where he later taught literature. He is much admired for his experimental writings, his 'social' poems, as well as for the diversity of his output. The present book comprises a chapter on Morgan's early vision poems (which have received scant critical attention hitherto); two on his hodoiporika, The Cape of Good Hope and The New Divan; a chapter on his deployment of the grotesque mode, centred chiefly on the Instamatic ...